Is There a Role for Probiotics in Liver Disease? - Robert S. Lo; Andrew S. Austin; Jan G. Freeman (The Scientific World Journal)
Intestinal microbiota plays an important role in health and disease. Alteration in its healthy homeostasis may result in the development of numerous liver disorders including complications of liver cirrhosis. On the other hand, restoration and modulation of intestinal flora through the use of probiotics is potentially an emerging therapeutic strategy. There is mounting evidence that probiotics are effective in the treatment of covert and overt hepatic encephalopathy, as well as in the prevention of recurrence of encephalopathy. The beneficial effect of probiotics also extends to liver function in cirrhosis, nonalcoholic fatty liver disease, and alcoholic liver disease. On the other hand, data associating probiotics and portal hypertension is scanty and conflicting. Probiotic therapy has also not been shown to prevent primary or secondary spontaneous bacterial peritonitis. Larger clinical studies are required before probiotics can be recommended as a treatment modality in liver diseases.